HARMONISASI RANCANGAN PERATURAN DAERAH OLEH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DI JAWA TENGAH - Monica Descariana; Jadmiko Anom Husodo (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
Harmonization of laws and regulations is an important part of a good national legal system. It aims to ensure that every legal product issued by the government can be in line with the principles, benefits, and rules of applicable law. In addition, harmonization of laws and regulations also serves to prevent legal products that are formally defective and overlap with other legal products. Harmonization of laws and regulations is regulated in Law Number 12 of 2022 concerning the Formation of Legislation and its amendments in Law Number 15 of 2019 and Law Number 13 of 2022. The writing of this article aims to examine the implementation of harmonization of regional scale laws and regulations at the Regional Office of Law and Human Rights in Central Java. The research method used is juridical-empirical research with a statutory approach and conceptual approach. In the discussion, the author finds that there are a number of problems in the harmonization process of Draft Regional Regulations and Draft Regional Head Regulations. These problems are caused by three factors, namely the discrepancy between the application and ratification of the harmonization of Regional Regulation and Regional Head Regulation, the facilitation of the harmonization of Regional Regulation and Regional Head Regulation, and the communication and coordination between the applicant for harmonization and the Regional Office of the Ministry of Law and Human Rights of Central Java.